Institutional structures for student-inclusivity in quality assurance promotion in higher education: The case of one university in Zimbabwe - Nkala, P.; Ncube, M. (South African Journal of Higher Education, 2020)
Researchers have investigated co-curricular and extracurricular activities associated with student learning and personal development but neglected exploring levels of students’ involvement. IHLs oftentimes have no structures responsible for quality assurance (QA). Research should focus on specific structures, activities and the frequency of student involvement. Although Zimbabwe Council for Higher Education superintends over QA processes, it remains unclear which/how institutional structures foster student inclusivity in QA processes. Pragmatic research, marked by mixed methods was used to examine university QA structures for inclusivity. Science, Technology, Engineering and Mathematics IHLs were targeted and purposive sampling helped select 15 QA office(rs) and SRC in one STEM university. Primary data from questionnaires and key informant interviews were used. Structures governing IHLs are prescribed by Acts of Parliament and the current frequency of involvement depends on meetings scheduled for IHL structures. This constricts effective involvement. Minimal involvement occurs in prescribed structures although more satisfying involvement is in student-initiated social clubs and organisations. IHL legislative instruments should be amended to reflect diversity in higher education; allow university Councils to tailor-make IHL institutional/infrastructural structures to deliver on their mandates than rely on prescribed one size fits all. Such change will foster more satisfying involvement for student socio-academic success.